HMM based sensor fault detection in neuromuscular blockade control - Lemos, Joao M.; Magalhaes, Hugo; Mendonca, Teresa (ECC : 2007 European Control Conference : 2-5 July 2007, 2007)
The problem of embedding sensor fault tolerance in the control of neuromuscular blockade of patients subject to anesthesia for surgery is considered. A hidden Markov model whose state, assumed unavailable for direct observation, is estimated using a nonlinear filtering algorithm (special case of Baum's algorithm), is proposed for detecting the faults. The resulting algorithm is illustrated by simulations with realistic models of neuromuscular blockade.